Konsumsi dalam Islam - Abd Ghafur (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2016)
Consumption is essentially out something in order to meet the needs. Consumption includes purposes, pleasure and luxury. Pleasure or beauty permitted as long as not excessive. Consumption according to a Muslim is merely intermediaries to add strength to obey God, which has a positive indication in his life. Someone Muslims would not hurt himself in the world and in the Hereafter, that it allows him to obtain and fulfill its consumption at a level beyond the limit, to keep them busy chasing and enjoy the pleasures of the world so as to neglect its primary task in this life. In Islam, the purpose of consumption is not a concept but a benefit unilitas (maslahah). The maslahah attainment is the goal of al-maqa>s}idus-of shari’ah. Unilitas concept is very subjective because it contradicts the fulfillment or wants, and the concept maslahah relatively more objective because contrary to the fulfillment or needs. Maslahah filled based on rational considerations normative and positive, then there are criteria on an economic good that discount maslahah or not. As determined unility more subjective because it differs from one person to another.